Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Usahatani Pinang Kecamatan Sawang Kabupaten Aceh Utara - Mawardati Mawardati (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. This research was conducted at the betel palm farming in Sawang subdistrict, North Aceh from May to July 2014. The purpose of this study was to determine the factors that affect betel palm farming income at Sawang subdistrict in North Aceh district of Aceh Province.This study uses primary data to be analyzed. Determination of the sample villages determined by purposive sampling, while the selection of sample units was done by using simple random sampling. The analytical method used is the method of multiple linear regression analysis. The analysis showed that the amount of capital production and the selling price very significant influence on betel palm farming income Sawang subdistrict in North Aceh district of Aceh province.